Analysis of the Graduate Studies in Different Disciplines Prepared for Music Education in Turkey - Oztutgan, Zuluf; Oztutgan, Kaan (Asian Journal of Education and Training, 2020)
This qualitative research is a descriptive study aiming to analyze the graduate studies in different disciplines prepared for music evaluation and to reveal the current situation in TurkeyThe sample of the study involves 25 graduate theses in different disciplines which are in the database of the National Thesis Center and defended in line with music education field. These theses were examined with content analysis and 10 criteria as follows: thesis type, its university, recearcher’s gender, publication year, title of advisor, its institute, its department, research area, research model and research class. The findings were interpreted in tables by calculating the frequency and percentage. The findings reveal that 76% of the examined theses in the scope of this study are master’s (MA), 20% doctorate (PhD) and 4% specialty in medicine theses. Most of the MA theses were prepared in Hacettepe University, and most of the PhD theses were prepared in Ankara University and the specialty in medicine thesis was completed in Gaziosmanpaşa University. In addition, most of these theses were written by female researchers and the number of theses in different disciplines prepapred for music education in Turkey is not numerous. Music education and preschool education were associated, and most of the PhD theses had equal distribution in the fields of Education Policies, Preschool Education, Mathematics Education, Empathic Skills and Sociology. Lastly, it was revealed that most of the theses were prepared based on descriptive model and quantitative approach.